2012
DOI: 10.1089/apc.2012.0198
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Characteristics Associated with Sexual Risk Behavior Among MSM in Committed Relationships

Abstract: Understanding situations that increase HIV risk among men who have sex with men (MSM) requires consideration of the context in which risky behaviors occur. Relationships are one such context. This study examines the presence and predictors of unprotected anal intercourse (UAI) in the past 3 months among 566 MSM couples. A majority of couples allowed sex with outside partners. Overall, 65% of the sample engaged in UAI with primary partner, including nearly half of discordant couples. Positive relationship facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
95
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 42 publications
7
95
2
Order By: Relevance
“…Prior research indicates that a substantial proportion of male couples have established some form of a sexual agreement, and the results presented here from an online sample of partnered men confirm these findings (Crawford et al, 2001;Hoff et al, 2009Hoff et al, , 2012Mitchell, 2014a, b;Mitchell et al, 2012). The majority of respondents reported that they were monogamous, with just less than one-third reporting the allowance of sexual activity outside of the relationship with or without conditions (i.e., having an open sexual agreement).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Prior research indicates that a substantial proportion of male couples have established some form of a sexual agreement, and the results presented here from an online sample of partnered men confirm these findings (Crawford et al, 2001;Hoff et al, 2009Hoff et al, , 2012Mitchell, 2014a, b;Mitchell et al, 2012). The majority of respondents reported that they were monogamous, with just less than one-third reporting the allowance of sexual activity outside of the relationship with or without conditions (i.e., having an open sexual agreement).…”
Section: Discussionsupporting
confidence: 79%
“…However, Stephenson et al also found that partnered men who reported they were in an open relationship had higher odds of recent HIV testing, lower odds of perceiving themselves to be at low risk for HIV infection, and lower odds of being very confident in remaining HIV negative, relative to those who reported monogamy. For couples whose agreement allows anal sex with outside partners, there is an elevated risk for HIV and STI acquisition and/or transmission, particularly if the agreement permits UAI with partners who are either serodiscordant or of unknown serostatus (Crawford et al, 2001;Hoff et al, 2012). Hence, men in open agreements may be correctly identifying themselves at increased risk of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…High rates of sexual risk behavior for HIV (with primary and casual partners) (4, 5) and low rates of disclosure of episodes with casual partners to one's primary partner have been documented among men in same-sex relationships (6, 7). Previous studies have also documented that partnered MSM are more likely to engage in unprotected anal intercourse (UAI) and to have more frequent sex with their main partners, increasing the number of exposure episodes within main partnerships (3, 5, 8). Each of these factors points towards the necessity of targeted HIV prevention interventions for male couples.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research with male couples has found that relationship commitment, trust, and communication patterns are important to study and include for HIV prevention efforts. [39][40][41] To address this knowledge gap, the present study sought to: (1) describe, by type of substance, whether neither, one, or both partners in concordant HIV-positive and HIV-discordant male couples used that particular substance with sex within their relationship or outside of the relationship, respectively; (2) assess, by substance type, whether relationship characteristic differences existed between three groups of couples: those who did not use substances with sex within the relationship to those with one or both partners who did; and (3) assess, by substance type, whether relationship characteristic differences existed between three groups of couples: those who did not use substances with sex outside the relationship to those with one or both partners who did. Dyadic data for this analysis was collected in the USA from a nationwide cross-sectional Internet survey study about male couples' relationships and behaviors.…”
Section: Introductionmentioning
confidence: 99%